Modeling and Control of Micro-grid Powered by Solar and Wind Energies - Sameh Zenned; Emna Aridhi; Abdelkader Mami (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
The number of installations of Micro-Grid or intelligent micro power networks will increase to quadruple by 2020.The purpose is to reduce the cost and the consumption of electricity in transmission and distribution networks, using a hybrid system powered by solar and wind sources, as well as integrating storage devices. This paper reviews and discusses the Micro-Grid Model. It describes various Micro-Grid components and different configurations. It also presents the model of two generation units (Photovoltaic and Wind Turbine). Then, a comparative study of different battery types used for large-scale electricity storage is carried out, followed by a review of control strategies.